Rapid methane hydrate formation in aluminum honeycomb. (15th September 2019) - Li, Renliang; Liu, Daoping; Yang, Liang; Cui, Guomin; Wang, Juan; Wang, Xin; Liu, Zhenzhen
Graphical abstract: Highlights: The channels of aluminum honeycomb (AH) can be considered as micro-vessels for the formation of gas hydrates. Large surface area of AH provided sufficient nucleation sites for hydrate nucleation. The excellent thermal conductivity of the metallic surface facilitates dissipation of the hydrate heat. SDS-AH system can store more methane with the higher hydrate formation rate compared to SDS solution. Abstract: In order to investigate the effect of metal honeycomb on the formation kinetics of methane hydrate, gas consumption experiments were conducted in a stainless steel vessel filled with sodium dodecyl sulfate (SDS) and aluminum honeycomb (AH) at 274.2 K in the pressure range 5.0–9.0 MPa. The honeycomb structure provides several interconnected channels with large rough surfaces for the promotion of hydrate nucleation. Meanwhile, the excellent thermal conductivity of the metallic surface facilitates dissipation of the hydrate heat. The honeycomb channels can be considered as micro-vessels for the formation of gas hydrates, and each channel provides a "free-unimpeded thermal conduction surface" for heat transfer in the hydration system. When AH is introduced in the SDS system, the methane consumption and its rate surpassed the values recorded in the absence of AH. The maximum gas consumption and the rate reached 157.0 ± 1.9 cm 3 ·cm −3 and 29.65 cm 3 ·cm −3 ·min −1, respectively. Comparison with the SDS system under similar conditions revealed that the maximum gas consumption rates increased by 9.62–14.30%. We hope this work provides new insights into the kinetic behavior of the formation of gas hydrates in metal honeycombs.